2021
DOI: 10.1590/1806-9479.2021.220439
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Colombian Andean farmers on climate change and mitigation and adaptation strategies

Abstract: This article presents the findings of research conducted in a rural community located in Norte de Santander Department, Colombia, on farmers' representations of the impacts of climate change. The analysis of the behavior of temperature and average rainfall in the period 1985-2015 was put together concerning the local knowledge of the farmers. The approach was developed through 56 multiple choice questions surveys done to 144 producers intentionally selected from a group of 1,933 farmers, analyzed with descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…An even larger majority (86%) indicated that Caribbean nations must make a large-scale effort to protect people's health in the wake of a changing climate (Drewry et al, 2022). A survey of Colombian Andean farmers found that they perceive climate change to be harming their health in a variety of ways (Rodríguez et al, 2020). For example, 41% said that increased heat is causing sleep disruptions, and a number also perceived higher rates of illnesses caused by climate change, including diarrhea (67%), dengue (43%), chikungunya (40%), Zika (34%), and allergies (27%).…”
Section: Other Regionsmentioning
confidence: 99%
“…An even larger majority (86%) indicated that Caribbean nations must make a large-scale effort to protect people's health in the wake of a changing climate (Drewry et al, 2022). A survey of Colombian Andean farmers found that they perceive climate change to be harming their health in a variety of ways (Rodríguez et al, 2020). For example, 41% said that increased heat is causing sleep disruptions, and a number also perceived higher rates of illnesses caused by climate change, including diarrhea (67%), dengue (43%), chikungunya (40%), Zika (34%), and allergies (27%).…”
Section: Other Regionsmentioning
confidence: 99%